CAMEL vs discriminant, a risk analysis to the Venezuelan financial system (2020)
This paper presents the credit ratings of the institutions belonging to the Venezuelan financial system at the end of the first half of 2010, obtained by applying two methods: the first known as CAMEL and the second through a statistical technique called analysis discriminant, the latter will qualify for financial institutions in risk categories, form a profile that shows the most representative feature of the category and quantify the probability of belonging to a rating. This research does not establish whether one model is better than the other, but show that you can supplement purely descriptive analysis multivariate analysis, applied to an area of knowledge that has been little exploited in Venezuela, allowing to inform the public at large , the statistical techniques used in risk.